The Dialectic of Muslim Clothing: Between Shariah Compliance and The Hijab Trend with Implications For Sexual Harassment - Hapsari, Aprilia Putri (Universitas Islam Negeri (UIN) Mataram, 2024)
In today’s era, diverse clothing trends disseminate widely via social media, establishing new fashion norms. One prominent trend is jilboobs, which has sparked concern among researchers due to its divergence from Islamic dress codes for women. This raises questions about the relevance of Quranic verses and hadith on attire in the age of globalization. Researcher investigates whether the jilboobs trend, contrary to legal dress norms, correlates with heightened incidents of sexual harassment. Employing phenomenological research with qualitative methods including surveys and interviews, this study finds: (1) Islamic dress laws based on Quranic principles and hadith are timeless and universally applicable, serving to safeguard Muslim women from harassment. (2) The jilboobs trend significantly increases the risk of sexual harassment against Muslim women.